The Black Woman Native Speaking Subject: Reflections of a Black Female Professor in Canada - Davis, Andrea (Atlantis)

(untitled) (Mount Saint Vincent University, 2018)
This paper interweaves literary and feminist theories alongside personal life stories to demonstrate the collapse of the boundaries of the personal and the intellectual in the pedagogical practices of Black female professors. The paper suggests that acknowledging the precariousness of performing one’s Blackness in university classrooms presents new possibilities for shared learning.